2022
DOI: 10.1002/pchj.525
|View full text |Cite
|
Sign up to set email alerts
|

Stable abnormalities of contrast discrimination sensitivity in subthreshold depression: A longitudinal study

Abstract: Subthreshold depression (StD), as a subclinical state, is highly prevalent and increases the risk for developing major depressive disorder (MDD). Although several studies have reported deficits of contrast sensitivity in MDD patients, it is unclear whether individuals with StD could demonstrate deficits of contrast sensitivity and whether the deficits could remain stable over time. Here we used a contrast discrimination task (a suprathreshold task) and a contrast detection task (a near‐threshold task) to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…We found that the depressive symptoms of the StD group significantly decreased from the first measurement to the second measurement. Such reductions of depressive symptoms were also reported in previous studies (Chen et al, 2022;Hegel et al, 2006;Hermens et al, 2004;Jeuring et al, 2016;Liao et al, 2022;Mei et al, 2020;van der Aa et al, 2015). The reduction may originate from individual characteristics, such as resilience and neuroticism, in some participants.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We found that the depressive symptoms of the StD group significantly decreased from the first measurement to the second measurement. Such reductions of depressive symptoms were also reported in previous studies (Chen et al, 2022;Hegel et al, 2006;Hermens et al, 2004;Jeuring et al, 2016;Liao et al, 2022;Mei et al, 2020;van der Aa et al, 2015). The reduction may originate from individual characteristics, such as resilience and neuroticism, in some participants.…”
Section: Discussionsupporting
confidence: 86%
“…The results suggested that the remitted individuals demonstrated higher accuracy in identifying face emotions than the healthy individuals and the currently depressive individuals. On the other hand, trait-dependent abnormalities have also been reported for some psychophysical biomarkers (e.g., Chen et al, 2022;Douglas et al, 2012;Milders et al, 2010;Ruhe et al, 2019) and biological markers (e.g., Elliott et al, 2012;van der Vinne et al, 2019;van Eijndhoven et al, 2013;Xiong et al, 2021). For example, Milders et al (2010) investigated the stability of emotion recognition for patients with unipolar depression by a longitudinal design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of a diminished contrast sensitivity in a larger cohort of MDD patients aligns with the results of previous studies [5,8], which also reported reduced visual contrast discrimination performance and contrast sensitivity in MDD. Accordingly, Chen et al [57] showed attenuated contrast discrimination sensitivity in patients with subthreshold depression. The observed reduced contrast sensitivity could reflect an altered dopaminergic neurotransmission involved in the pathophysiology of MDD [5,58].…”
Section: Discussionmentioning
confidence: 99%